ANALISA TINGKAT UPAH PEKERJA WANITA DI PABRIK ROKOK (Study Pada Perusahaan Rokok “EMPAT SAUDARA ABADI” di Desa Jambi Kecamatan Baron, Kabupaten Nganjuk) - Ery Kisworo (Jurnal Ekonomi Pembangunan, 2014)
The purpose of this study was to find out how much the level of wages of women workers in the factory cigarette "Empat Saudara Abadi" in the village of Jambi District of Baron Nganjuk, in this study the author took the hypothesis is suspected that there is influence between the level of education, age, length of service and number of dependency family against wage levels. The technique used is by using a percentage formula and using multiple linear regression, using the F test and t test and classical assumption. Based on the empirical results mentioned that variable levels of education, longer working, and the number of family dependents burden, affect the level of wages.